Are oaks locally adapted to serpentine soils? - Branco, Sara (2019)
Serpentine soils are extreme habitats known to be involved in processes of local adaptation and speciation of plants. Here I use a greenhouse reciprocaltransplant experiment to compile baseline data for describing patterns of serpentine local adaptation in Quercus ilex subsp. ballota (Holm Oak). I also tested the role of mycorrhizal fungi on the establishment and growth of seedlings on serpentine and non-serpentine soil. Non-serpentine seedlings grew more than serpentine seedlings in all treatments. Plants grew more on non-serpentine soil and mycorrhizal fungi positively infl uenced seedling growth. I did not fi nd evidence of better seedling performance in their home environment, suggesting the absence of local adaptation. However, I document signifi cant growth differences between serpentine and nonserpentine seedlings, which suggest physiological differences between seedlings from these two soil origins.